Tolvaptan induces body fluid loss and subsequent water conservation in normal rats - Kidoguchi, Satoshi; Kitada, Kento; Fujisawa, Yoshihide; Nakano, Daisuke; Yokoo, Takashi; Titze, Jens; Nishiyama, Akira (Journal of Pharmacological Sciences, 2022)
We have recently reported that the urea osmolyte-associated water conservation system is activated in fluid loss models such as high salt-induced natriuresis, renal injury-induced impaired renal concentrating ability, or skin barrier dysfunction-induced transepidermal water loss. The system consists of the interaction of multiple organs including renal urea recycling, hepato-muscular ureagenesis, and suppression of cardiovascular energy expenditure. Here, we determined the effect of pharmacological fluid loss induced by tolvaptan, a selective vasopressin V2 receptor antagonist, on water conservation. We evaluated the water conservation system in rats that consumed a control diet or a diet containing 0.1% tolvaptan. Tolvaptan increased urine volume on day 1, but this renal water loss then gradually decreased. Body water and osmolyte content were decreased by tolvaptan on day 1 but had normalized by day 7. Tolvaptan induced fluid loss on day 1, and the following restoration of body fluid on day 7 was associated with an increase in urea transporter A1-associated renal urea recycling. Tolvaptan did not affect hepato-muscular ureagenesis on day 1 and day 7, or cardiovascular energy expenditure during treatment. Thus, tolvaptan-induced fluid loss leads to activation of the water conservation system via renal urea recycling.
CRIS-Team Scopus Importer:2022-05-20
Keywords: Blood pressure; Body fluid; Cardiovascular energy expenditure; Tolvaptan; Urea